2015
DOI: 10.1002/admi.201500365
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Fabrication of PtCo Alloy Embedded in Nitrogen‐Doped Graphene Nanopores as Synergistic Catalyst for Oxygen Reduction Reaction

Abstract: embedded metal nanoparticles in nanopores is essential for catalytic investigation.In the present study, we demonstrate a general and scalable synthesis approach to PtCo nanoparticles embedded in nitrogen-doped graphene nanopores (PtCo/NPG) through direct in situ etching by platinum phthalocyanine (PtPc) and cobalt phthalocyanine (CoPc) in pristine graphene. To our knowledge, no attention has been given to the use of PtPc as precursor to alloy formation. Nitrogen-rich PtPc and CoPc supply abundant N sources, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…In addition to the inorganic active components (e.g . , metal [89] , alloys [90,91] , oxides [92,93] , carbides [94] , sulfides [95] , hydroxides [96][97][98] , hydrofluoride [99] , hydroxysulfides [87] , and oxysulfides [100] , etc. ), nanocarbon materials also afford favorable surfaces for the tunable deposition of organic active components, such as graphitic carbon nitrides (g-C 3 N 4 ) [101][102][103] , metal organic frameworks [104] , covalent organic framework [105,106] , metal porphyrins/phthalocyanines [107,108] , etc.…”
Section: Modify the Incorporation Of Active Componentsmentioning
confidence: 99%
“…In addition to the inorganic active components (e.g . , metal [89] , alloys [90,91] , oxides [92,93] , carbides [94] , sulfides [95] , hydroxides [96][97][98] , hydrofluoride [99] , hydroxysulfides [87] , and oxysulfides [100] , etc. ), nanocarbon materials also afford favorable surfaces for the tunable deposition of organic active components, such as graphitic carbon nitrides (g-C 3 N 4 ) [101][102][103] , metal organic frameworks [104] , covalent organic framework [105,106] , metal porphyrins/phthalocyanines [107,108] , etc.…”
Section: Modify the Incorporation Of Active Componentsmentioning
confidence: 99%
“…Nanoporous graphene (NPG), which possesses unique porous structure, large specific surface area, and fast charge transport mobility, has various applications in molecular sieving, DNA sequencing, and electrochemical sensors . Our previous study has indicated that the introduction of nanoscale pores into graphene sheets can increase the amount of defects and edges, which can provide more anchors and enable metal nanoparticles strongly interact with the edge planes . Meanwhile, the open laminar structure of NPG may also help the access of electrolyte and shorten the ion diffusion pathway to facilitate mass transport .…”
Section: Introductionmentioning
confidence: 99%
“…The HR‐TEM image (Figure 2d) shows the sputtered Pt and Co nanoparticles with clear and well‐defined lattice fringes with a distance 0.22 nm, which is in accordance with the spacing of (111) planes for disordered Pt‐Co alloy. [ 37,38 ] The HAADF‐STEM images in Figure 2e coupled with EDX mappings validate that the Pt, Co, and Nafion ingredients are evenly distributed across the carbon nanotube substrates.…”
Section: Resultsmentioning
confidence: 74%